Implementasi Konsep Etika: Relasi Guru Dan Siswa Dalam Kitab Ta’lim Al-Muta’allim Di Pondok Pesantren Roudlotul Khuffadz - Hasbi Siddik; St Umrah (Al-Fikr: Jurnal Pendidikan Islam, 2017)
Ethics can be the values or norms that become a guideline for a person or group in regulating their behavior. In this study, the researchers took the Raudhatul Khuffadz Aimas Islamic boarding school in Sorong Regency as a study site. The Book of Ta'lim al-Muta’allim. Relationship ethics to the teacher or religious teacher and teacher in the environment of the Raudhatul Khuffadz Islamic Boarding School although not yet fully achieved because of differences in the character of each individual student. However, as the results of interviews with board administrators that it is not an inhibiting factor in realizing what they have learned either through studying the book itself or through studies guided by the cleric and his cleric. They not only realize it in the hut environment but also formal education and also when they return to their respective homes.